USE OF MOBILE-APP FOR OLDER PEOPLE WITH CHRONIC DISEASES TO COPE WITH THE COVID-19 PANDEMIC: A LITERATURE REVIEW (Jurnal Mitra Kesehatan, 2021)
Introduction: The older people with chronic diseases are one of the populations that have a susceptibility to COVID-19. The community-based program that help older people manage their lifestyle was postponed due to avoiding crowds and physical contacts. This literature review aims to describe a mobile-app for the older people with chronic diseases and its benefits. This literature review aims to describe a mobile-app for the older people with chronic diseases and its benefits. Method: The method used in this study is a literature review. This study is analyzed by selecting some literature that is relevant to the purpose of writing in order to obtain new conclusions. Online databases used are ProQuest, Pubmed and Science Direct starting from 2019 to 2021. The keywords used to sort articles in this study are: 1) older people, 2) mobile app, 3) COVID-19. Results: There was ten selected articles that analyzed. This literature review resulted in three main themes in the use of mobile-apps for the older people with chronic diseases, namely (1) monitoring of chronic diseases and COVID-19, (2) management of chronic diseases and COVID-19, and (3) the perspective of older people caregivers. The implication for nursing services is that nurses can disseminate information and provide interventions by minimizing physical contact. In addition, these results also have implications for the scope of nursing education, namely adding reference material for studies in health information systems courses. Conclusion: These results can be used as a basis for creating mobile-app-based educational media, monitoring, and self-management of chronic diseases for the older people and their caregivers.